1989
DOI: 10.1111/j.1365-2648.1989.tb00908.x
|View full text |Cite
|
Sign up to set email alerts
|

Health assessment of the elderly at home: the case for shared learning

Abstract: This paper reports findings from a collaborative research project (Buckley & Runciman 1985) which examined, using video studies and questionnaires, the scope and content of health assessment of old people at home and the views and feelings of different groups of health professionals towards visiting old people at home. The study sample included student and experienced health care workers and a number of elderly people; seven professional groups were represented. A prompt list summarizing key content of health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…53 This was not the case for our study, where problems reflecting cognitive difficulties showed similar or higher agreement than those reflecting motor skills, although difficulties before SAP implementation were almost universally poorly detected. It may be, as previous studies have suggested, 3 that different professional groups have a tendency to identify different conditions or problems. One challenge for the SAP will be to enable different professionals to become aware of the existence of a range of conditions and to accept the assessments made by others.…”
Section: What Is Known Alreadymentioning
confidence: 89%
“…53 This was not the case for our study, where problems reflecting cognitive difficulties showed similar or higher agreement than those reflecting motor skills, although difficulties before SAP implementation were almost universally poorly detected. It may be, as previous studies have suggested, 3 that different professional groups have a tendency to identify different conditions or problems. One challenge for the SAP will be to enable different professionals to become aware of the existence of a range of conditions and to accept the assessments made by others.…”
Section: What Is Known Alreadymentioning
confidence: 89%
“…This was most strikingly illustrated by the concerns of day hospital professional groups not represented in the day centres, who felt that patient care might be severely compromised. Runciman (1989) studied the approach of seven different health professional groups to the assessment of older people’s needs. She found that although there was a high degree of overlap in their perceptions, there were also significant differences which strongly reflected particular professional orientations.…”
Section: Discussionmentioning
confidence: 99%
“…Staff reported that it gave rise to significant variations in the perceived number of subsequent services or interventions that might be required. Most staff were inclined to the view that service user needs were being identified, but research in this area has indicated the potential for differences among health staff (Runciman, 1989) and, more significantly, between social work and health staff (McKerron, 2001), the latter being more likely to produce assessment outcomes requiring further intervention or services.…”
Section: The Assessment Toolmentioning
confidence: 99%